QoE-Oriented Mobile Edge Service Management Leveraging SDN and NFV - Peng, Shuping; Fajardo, Jose Oscar; Ruiz, Cristina; Turyagyenda, Charles; Wilson, Mick; Vadgama, Sunil (Mobile Information Systems, 2017)
5G envisages a “hyperconnected society” where trillions of diverse entities could communicate with each other anywhere and at any time, some of which will demand extremely challenging performance requirements such as submillisecond low latency. Mobile Edge Computing (MEC) concept where application computing resources are deployed at the edge of the mobile network in proximity of an end user is a promising solution to improve quality of online experience. To make MEC more flexible and cost-effective Network Functions Virtualisation (NFV) and Software-Defined Networking (SDN) technologies are widely adopted. It leads to significant CAPEX and OPEX reduction with the help of a joint radio-cloud management and orchestration logic. In this paper we discuss and develop a reference architecture for the orchestration and management of the MEC ecosystem. Along with the lifecycle management flows of MEC services, indicating the interactions among the functional modules inside the Orchestrator and with external elements, QoS management with a focus on the channel state information technique is presented.
Keywords: QoE; Mobile Edge Service Management; SDN and NFV